(untitled) - Abramowitz, Alan (New York, 2004)
Written by one of the top scholars in the field, this text will help readers understand the continued disengagement of American citizens from the electoral process, as well as the reasons for the ongoing ideological realignment of the Democratic and Republican parties. In the process, students are introduced to some of the theoretical approaches and analytic techniques commonly used in research on elections and voting behavior
Keywords: Elections,Voting,Democracy; United States,United States,United States